Advances in anion binding and sensing using luminescent lanthanide complexes. Issue 8 (26th January 2021) - Bodman, Samantha E.; Butler, Stephen J.
Abstract : This minireview highlights advances in anion binding and sensing using luminescent lanthanide(iii ) complexes. Abstract : Luminescent lanthanide complexes have been actively studied as selective anion receptors for the past two decades. Ln(iii ) complexes, particularly of europium(iii ) and terbium(iii ), offer unique photophysical properties that are very valuable for anion sensing in biological media, including long luminescence lifetimes (milliseconds) that enable time-gating methods to eliminate background autofluorescence from biomolecules, and line-like emission spectra that allow ratiometric measurements. By careful design of the organic ligand, stable Ln(iii ) complexes can be devised for rapid and reversible anion binding, providing a luminescence response that is fast and sensitive, offering the high spatial resolution required for biological imaging applications. This review focuses on recent progress in the development of Ln(iii ) receptors that exhibit sufficiently high anion selectivity to be utilised in biological or environmental sensing applications. We evaluate the mechanisms of anion binding and sensing, and the strategies employed to tune anion affinity and selectivity, through variations in the structure and geometry of the ligand. We highlight examples of luminescent Ln(iii ) receptors that have been utilised to detect and quantify specific anions in biological media ( e.g. human serum), monitor enzyme reactions in real-time, and visualise target anions with high sensitivity in living cells.